Schizoanalytic pedagogical framework: A rhizomatic approach to teaching languages - Daisy Gohain; David Paul (MethodsX)
The Schizoanalytic Pedagogical Framework (SPF) is one of the revolutionary reconceptualizations of language pedagogy based on the poststructuralist, anti-Oedipal thought of Deleuze and Guattari. The present paper empirically substantiates SPF using its demonstration in multilingual English classrooms across both quantitative and qualitative outcomes. The rhizomatic structure of the framework dismantles central authority, values affective intensity, and enables students to collectively create meaning through four processes: Break, Map, Connect, and Create. These stages foster the dismantling of dominant linguistic regimes, enabling learners to craft individualized, interdisciplinary assemblages of meaning. Through affect-mediated, creative engagements, learners are positioned as desiring-subjects rather than passive recipients, rendering the pedagogical space a site of expressive experimentation rather than disciplinary normalization. The framework supports learner-focused, affectively charged encounters with language, privileging expression, multiplicity, and relationality. Empirical applications within English language classrooms reveal marked improvements in learner motivation, cultural resonance, and communicative competency. Being an adaptive and generative model, SPF repositions language learning back into an ecosophic and minoritarian pedagogy where language learning occurs not as a codified system to be mastered but as a lived aesthetic practice of collective sense-making and transversal becoming.• Advances an affect-mediated, learner-centric paradigm in language acquisition.• Incorporates rhizomatic and schizoanalytic theoretical models to inform language instruction practices.• Endorses the generation of dynamic, adaptable, and creatively situated learning outputs.